Metabolomics in Primary Open Angle Glaucoma: A Systematic Review and Meta-Analysis - Tang, Yizhen; Shah, Simran; Cho, Kin-Sang; Sun, Xinghuai; Chen, Dong Feng (Frontiers in Neuroscience, 2022)
Glaucoma is a leading cause of blindness worldwide. It is emerging that primary open angle glaucoma (POAG), the most common form of glaucoma, may be associated with significant metabolic alternations, but the systemic literature review and meta analysis in the area has been missing. Altered metabolomic profiles in the aqueous humor and plasma may serve as possible biomarkers for early detection or treatment targets. In this paper, we performed a systematic meta-analysis of the current literature surrounding the metabolomics of POAG patients and metabolites associated with the disease. Results suggest several metabolites found to be specifically altered in POAG patients, suggesting broad generalizability and pathways for future research.